Contribution of GlyR α3 Subunits to the Sensitivity and Effect of Ethanol in the Nucleus Accumbens - San Martin, Loreto S.; Armijo-Weingart, Lorena; Araya, Anibal; Yévenes, Gonzalo E.; Harvey, Robert J.; Aguayo, Luis G. (Frontiers in Molecular Neuroscience, 2021)
The glycine receptor (GlyR), a ligand-gated ion channel, is critical for inhibitory neurotransmission in brainstem, spinal cord and in supraspinal regions. Recent data from several laboratories have shown that GlyRs are expressed in the brain reward circuitry and that alpha1 and alpha2 are the principal subunits expressed in the nucleus accumbens (nAc). In the present study, we studied the sensitivity to ethanol of homomeric and heteromeric alpha3 GlyR subunits in HEK293 cells and dissociated neurons from the nAc. Finally, we explored ethanol-related behaviors in a Glra3 knockout mouse (Glra3-/-). Studies in HEK293 cells showed that while homomeric alpha3 GlyR subunits were insensitive to ethanol, heteromeric alpha3beta GlyR subunits showed higher sensitivity to ethanol. Additionally, using electrophysiological recordings in dissociated accumbal neurons, we found that the glycine current density increased in Glra3-/- mice and the GlyRs were less affected by ethanol and picrotoxin. We also examined the effect of ethanol on sedation and drinking behavior in Glra3-/- mice and found that the duration in the loss of righting reflex (LORR) was unchanged compared to wild-type (WT) mice. On the other hand, using the drinking in the dark (DID) paradigm, we found that Glra3-/- mice have a larger ethanol consumption compared to WT mice, and that this was already high during the first days of exposure to ethanol. Our results support the conclusion that heteromeric alpha3beta , but not homomeric alpha3, GlyRs are potentiated by ethanol. Also, the increase in GlyR and GABAAR mediated current densities in accumbal neurons in the KO mice support the presence of compensatory changes to alpha3 knock out. The increase in ethanol drinking in the Glra3-/- mice might be associated to the reduction in beta and compensatory changes in other subunits in the receptor arrangement.